Pulsating aurora and magnetic Pi(c) pulsations ... - Craven, M. (University Of Tasmania, 2023)
This thesis is the result of a year spent at Macquarie Island (54¬¨‚àû 30'S, 158¬¨‚àû57'E) on the 1983 Australian National Antarctic Research Expedition, collecting data pertaining to pulsating aurora and geomagnetic Pi(c) micropulsations. Data was collected with a 0.2s sampling period and stored by an LSI-11 microcomputer on floppy disks for the bulk of the year, then on RLO2 hard disk for the final months. Strong peak-to-peak correlations were observed between the optical pulsating aurora, measured at the N2+ 4278A band head emission, and the micropulsations. Average time delays were determined to be 0.6s and 0.3s for the D and H Pi(c) micropulsations respectively, trailing the optical fluctuations. The H component Pi(c) micropulsations will be shown to be consistent with a precipitation induced Hall conductivity enhancement of the westward E-region auroral electrojet during the greater part of this activity. The sign, or phase, of the 4278A/H micropulsation correlation function was in close agreement with ...